The effect of bean sprout waste and feeding time to the chemical composition of Garut lamb - Siti Aslimah; Mohammad Yamin; Dewi Apri Astuti (Faculty of Animal Science, Universitas Brawijaya, 2019)
This research aims to determine the chemical composition of Garut lamb fed with bean sprout waste along with different feeding time. The subjects of this research were 12 Garut sheep aged 6 to 7 months with the initial weight at 16.76 ± 2.09 kg (co-efficient of variation = 12.47%). Both of the given feed were consisted of 14% isopro-tein and 65% iso-total digestible nutrients (iso-TDN), which divided into R1 (40% for-age + 60% concentrate 1) and R2 (40% bean sprout waste + 60% concentrate 2). The research was conducted in a completely randomized design with 2x2 factorial and rep-licated 3 times. The first factor was two feed types (R1 and R2), while the second factor was the feeding time (morning and afternoon). The obtained chemical composi-tion data of lamb were then analyzed with ANOVA. The results showed that the chem-ical composition of Garut lamb fed with bean sprout waste was similar to the lamb fed with forage. Moreover, the different feeding time did not show significant differences as well (P>0.05), and there was no interaction between type of feed with feeding time to the chemical composition of Garut meat. The water, fat, protein, and ash content of Garut lamb fed with bean sprout waste were 77.09 ± 2.07%; 1.60 ± 0.69%; 16.66 ± 0.38%; and 0.42 ± 0.41%, while fed with forage were 73.25 ± 1.66%; 3.27 ± 2.02%; 17.68 ± 1.82%; and 0.48 ± 0.20%, respectively.